Pristine environments harbor a new group of oligotrophic 2,4-dichlorophenoxyacetic acid-degrading bacteria. - Kamagata, Y (1997)
2,4-Dichlorophenoxyacetic acid (2,4-D)-degrading bacteria were isolated from pristine environments which had no history of 2,4-D exposure. By using 2,4-D dye indicator medium or 14C-labeled 2,4-D medium, six strains were isolated from eight enrichment cultures capable of degrading 2,4-D. Phylogenetic analyses based on 16S ribosomal DNA (rDNA) sequencing and physiological properties revealed that one isolate from Hawaiian volcanic soil could be classified in the genus Variovorax (a member of the beta subdivision of the class Proteobacteria) and that the other five isolates from Hawaiian volcanic soils, Saskatchewan forest soil, and Chilean forest soil have 16S rDNAs with high degrees of similarity to those of the Bradyrhizobium group (a member of the alpha subdivision of the class Proteobacteria). All the isolates grow slowly on either nutrient media (0.1 x Bacto Peptone-tryptone-yeast extract-glucose [PTYG] or 0.1 x Luria broth [LB] medium) or 2,4-D medium, with mean generation times of 16 to 30 h, which are significantly slower than previously known 2,4-D degraders. Nutrient-rich media such as full-strength PTYG and LB medium did not allow their growth. PCR amplification using internal consensus sequences of tfdA (a gene encoding an enzyme for the first step of 2,4-D mineralization, found in pJP4 of Alcaligenes eutrophus JMP134 and some other 2,4-D-degrading bacteria) as primers and Southern hybridization with pJP4-tfdA as a probe revealed that the isolate belonging to the genus Variovorax carried the tfdA gene. This gene was transmissible to A. eutrophus JMP228 carrying a plasmid with a mutant tfdA gene. The other five isolates did not appear to carry tfdA, and 2,4-D-specific alpha-ketoglutarate-dependent dioxygenase activity could not be detected in cell lysates. These results indicate that 2,4-D-degrading bacteria in pristine environments are slow-growing bacteria and that most of their phylogenies and catabolic genes differ from those of 2,4-D degraders typically isolated from agricultural soils or contaminated environments.